2018
DOI: 10.1002/smll.201802089
|View full text |Cite
|
Sign up to set email alerts
|

Temporally Programmed Disassembly and Reassembly of C3Ms

Abstract: Responsive materials, which can adapt and operate autonomously under dynamic conditions, are a stepping stone towards functional, life-like systems inspired by fueled self-assembly processes in nature. Complex coacervate core micelles (C3Ms) comprising oppositely charged macromolecules constitute a novel class of polymeric micelles ideally suited for use as responsive nanoscopic delivery vehicles of hydrophilic and hydrophobic cargo. To fully exploit their potential, it is important that the C3Ms form and fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
(37 reference statements)
0
30
0
1
Order By: Relevance
“…To demonstrate the proof-of-principle, C3Ms have been exposed to controlled environments, which were induced to undergo an autonomous variation in the solution pH through the production of either base or acid, to disassemble and assemble the C3Ms within a predesignated timeframe reversibly. Specifically, C3Ms consisting of poly( N -methyl-2-vinylpyridinium iodide copolymer (PM2VP- b -PEO) and poly [9,9′-bis(3′-sodium propanoate)fluoren-2,7-yl] (cPF) were prepared at high pH in the presence of the enzyme urease, loaded with Dox, and programmed for transient disassembly by means of the urease-catalyzed hydrolysis of urea [ 153 ]. The water-soluble, conjugated polyelectrolyte cPF was negatively charged in the initial basic solution and, thus, complexed with the positively charged block copolymer.…”
Section: Biotechnological Applications Of C3msmentioning
confidence: 99%
“…To demonstrate the proof-of-principle, C3Ms have been exposed to controlled environments, which were induced to undergo an autonomous variation in the solution pH through the production of either base or acid, to disassemble and assemble the C3Ms within a predesignated timeframe reversibly. Specifically, C3Ms consisting of poly( N -methyl-2-vinylpyridinium iodide copolymer (PM2VP- b -PEO) and poly [9,9′-bis(3′-sodium propanoate)fluoren-2,7-yl] (cPF) were prepared at high pH in the presence of the enzyme urease, loaded with Dox, and programmed for transient disassembly by means of the urease-catalyzed hydrolysis of urea [ 153 ]. The water-soluble, conjugated polyelectrolyte cPF was negatively charged in the initial basic solution and, thus, complexed with the positively charged block copolymer.…”
Section: Biotechnological Applications Of C3msmentioning
confidence: 99%
“…Numerous synthetic complex coacervate-based droplets exist, [11][12][13][14][15][16][17][18] which are used to investigate the characteristics of membraneless organelles. 19,20 Examples of reversible complex coacervate droplets have been reported that form or dissolve upon a change in pH, 21 temperature, 19 salt or polymer concentration, 19,22 or in response to UV light 23 or an enzymatic reaction [24][25][26] . These models provide valuable information on the formation or dissolution of droplets.…”
mentioning
confidence: 99%
“…Voets seeks to understand how complex functionalities emerge from hierarchical self‐organization processes in (biological) soft matter, aiming ultimately to design, manufacture, and apply innovative lifelike materials. She was among the authors of a Communication in Angewandte Chemie on strain stiffening hydrogels and a Communication with inside back cover in Small on the programmed disassembly and reassembly of complex coacervate core micelles …”
Section: Awarded …mentioning
confidence: 99%